LEMAHNYA HUKUM TIPIKOR DI INDONESIA - Daffa, Gusti Alif (UNES Law Review, 2019)
This article aims to discuss the WEAK LAW OF CORRUPTION OF CRIMINAL ACTION IN INDONESIA (Corruption) to deal with corruption that is increasingly prevalent in Indonesia. Eradication of Corruption is intended to eradicate corruption that can trap corruptors and make them deterrent, as well as providing side effects in the form of preventing the emergence of new corruptors. The method used in writing this article is to use qualitative descriptive and Library Research. Qualitative descriptive is one of the types of research included in the type of qualitative research. The purpose of this study is to reveal events or facts, circumstances that occur directly by presenting what is happening as it is. This writing outlines the data that is happening, attitudes and views that occur in society, conflict between two or more parties, differences between facts that become a condition that arises. The aim of the descriptive qualitative research is in line with the problem formulation and research questions / identification of research problems. This is due to the purpose of this study will answer the questions previously raised by the formulation of the problem as well as research questions / problem identification. This goal also determines how you process or.